Promosi Kesehatan Masyarakat Berdasarkan Data Epidemiologi dan Dampaknya terhadap Penurunan Kasus Tuberkulosis: Tinjauan Sistematis - Rezki Ramdani; Yasinta Indah Widyaningsih; Salwah Suardi (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Tuberculosis (TB) remains a major global public health challenge, and effective disease control relies on the ability to target interventions to high-risk populations. Community health promotion based on epidemiological data offers a strategic approach to enhance case detection and reduce TB incidence through targeted community interventions. Articles for this systematic review were retrieved from Scopus, ScienceDirect, and Google Scholar using the keywords: “community health promotion,” “TB epidemiological data,” “active case finding,” “Digital Adherence Technologies,” and “community-based interventions.” Inclusion criteria encompassed publications from 2022–2025 that addressed the implementation of epidemiology-based health promotion, evaluation of community interventions, and the use of digital technologies to support TB case reduction. The review findings indicate that utilizing local data enables the identification of hotspots and high-risk populations, making community interventions more effective, while integrating digital technologies improves treatment adherence, early case detection, and resource allocation efficiency. Combining community education, engagement of local health cadres, and digital technologies enhances patient motivation and overall program effectiveness, although challenges such as infrastructure limitations, digital literacy, and program sustainability remain. Overall, epidemiology-based community health promotion supported by digital and community interventions offers an effective strategy to reduce TB cases, with success dependent on cross-sector integration, ongoing monitoring, and long-term commitment from stakeholders.